Magnetic-field-induced nematic-columnar phase transition in aqueous suspensions of goethite (alpha-FeOOH) nanorods - Lemaire, B.J.; Davidson, P.; Panine, P.; Jolivet, J.P. (Physical Review Letters, 2004)
Colloidal aqueous suspensions of goethite lath-shaped nanorods form nematic and isotropic phases. We show that they also display a 2D rectangular (c2mm) columnar phase at volume fractions phi larger than 15%. Interestingly, the nematic-columnar first-order transition can also be triggered by applying to the nematic phase a magnetic field of intensity decreasing with phi (1 T at 8.5%; 0.5 T at 12%). Single domains of the columnar phase were thus produced and their structure investigated by synchrotron x-ray scattering. This magnetic-field-induced transition is fully reversible and reproducible.